2020
DOI: 10.1002/elan.202060132
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Dioxide/Multi‐walled Carbon Nanotubes Composite Modified Pencil Graphite Sensor for Sensitive Voltammetric Determination of Propranolol in Real Samples

Abstract: A very effective electrochemical sensor for the analysis of propranolol was constructed using TiO2/MWCNT film deposited on the pencil graphite electrode as modifier. The modified electrode represented excellent electrochemical properties such as fast response, high sensitivity and low detection limit. The proposed sensor showed an excellent selective response to propranolol in the presence of foreign species and other drugs. The electrochemical features of the modified electrode were investigated by cyclic vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…EDX spectrum of NiO/PGE (Figure S2a) is evident for the presence of NiO NPs on the electrode surface [25,35]. EDX spectrum of MWCNT/PGE (Figure S2b), on the other hand, contains only C and O elements that appeared in the composite film [36]. In the case of NNaM/PGE (Figure S2c), the characteristic elements in the structure of NNaM clay were observed [37].…”
Section: Characterization Of Modified Electrodesmentioning
confidence: 97%
See 1 more Smart Citation
“…EDX spectrum of NiO/PGE (Figure S2a) is evident for the presence of NiO NPs on the electrode surface [25,35]. EDX spectrum of MWCNT/PGE (Figure S2b), on the other hand, contains only C and O elements that appeared in the composite film [36]. In the case of NNaM/PGE (Figure S2c), the characteristic elements in the structure of NNaM clay were observed [37].…”
Section: Characterization Of Modified Electrodesmentioning
confidence: 97%
“…NiO/PGE surface, on the other hand, it is seen that the chitosan molecules in the composite solution covered the layered and irregular graphite surface, NiO NPs stood like electrochemical perception points on this chitosan covered PGE surface [25,35]. The MWCNT/PGE surface is completely different from the bPGE surface due to MWCNTs' characteristic 3D structure (Figure1c) [36]. On the NNaM/PGE surface, it was observed that NNaM took a porous position outward on the surface covered with chitosan.…”
Section: Characterization Of Modified Electrodesmentioning
confidence: 97%
“…Other modified PGEs were manufactured by dip [17,61,69,87,88,90,92,127,132,133] or spin coating [48,[50][51][52]125,126,134]. Drop coating was applied to produce Mo 5 O 8 /PGE [34], Trypan blue-modified PGEs [44], different CNT-modified PGEs [47,57,58,68], or PGEs covered with various modifiers [41,49,62,65,135].…”
Section: Applications Of (Electro)chemically Modified Pges To the Vol...mentioning
confidence: 99%
“…As was already stated, modified PGEs have superior electrochemical performance characteristics when compared with the bare ones. For example, propranolol exhibited a small oxidation peak for the unmodified PGE, while for the MWCNT/PGE and TiO 2 /MWCNT/PGE, the peak currents were higher and the potentials shifted due to the presence of carbon nanotubes and TiO 2 nanoparticles, which enhanced the electroactive surface area and reduced the electron transfer resistance [132]. A similar behavior was observed for paroxetine, whose weak oxidation signal for the bare PGE increased with the rGO/PGE and furthermore for the PWA/rGO/PGE, along with a decrease in the peak potential [64].…”
Section: Applications Of (Electro)chemically Modified Pges To the Vol...mentioning
confidence: 99%
“…The most important part of each voltammetric system is the working electrode (WE). For propranolol determination, different types of solid electrodes were used, e.g., glassy carbon electrode (GCE) [13,14], graphite electrode (GE) [15,16], carbon paste electrode (CPE) [17,18], boron doped diamond electrode (BDDE) [19], and screen printed electrode (SPE) [20,21]. A recent trend in electrochemical methods has focused on the modification of solid electrodes (GCE, CPE, GE, and SPE) in order to improve their performance.…”
Section: Introductionmentioning
confidence: 99%